2015
DOI: 10.1007/s12253-015-9999-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Positive Margin and the Surgical Learning Curve in Non-Palpable Breast Cancer After Wire-Guided Localization – Prospective Study of 214 Consecutive Patients

Abstract: To investigate the most commonly used technique, the wire-guided localization (WGL) in non-palpable breast cancer. To analyze the effective factors on positive surgical margins in our practice and determine the surgical learning curve of this method. Prospective consecutive study was performed from January 2005 to December 2011. Inclusion criteria was a non-palpable breast lesion with malignancy on preoperative histology. All lesions were localized by ultrasound or stereotactic guided wire placement. Margins 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…5 WGL relies on surgical experience to visually estimate the extent of resection needed to clear the lesion, which may lead to increased re-operation rate and possibly increased risk of recurrence. 6,7 Finally, WGL requires separate lymphatic mapping to identify sentinel nodes which is often done using an arguably inferior subareolar radioisotope injection technique to avoid interacting with the hookwire. 8 A range of other occult breast lesion localization techniques exist, each with its own inherent strengths and weaknesses, including intraoperative US, carbon track injection and radioisotope occult lesion localization (ROLL) using radioactive iodine seeds (ROLLIS), but only sentinel node and occult lesion localization (SNOLL) combines SN localization in a single procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 WGL relies on surgical experience to visually estimate the extent of resection needed to clear the lesion, which may lead to increased re-operation rate and possibly increased risk of recurrence. 6,7 Finally, WGL requires separate lymphatic mapping to identify sentinel nodes which is often done using an arguably inferior subareolar radioisotope injection technique to avoid interacting with the hookwire. 8 A range of other occult breast lesion localization techniques exist, each with its own inherent strengths and weaknesses, including intraoperative US, carbon track injection and radioisotope occult lesion localization (ROLL) using radioactive iodine seeds (ROLLIS), but only sentinel node and occult lesion localization (SNOLL) combines SN localization in a single procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, wire migration or dislodgement can occur, 4 and many report experiencing physical and psychological discomfort as a result of the wire 5 . WGL relies on surgical experience to visually estimate the extent of resection needed to clear the lesion, which may lead to increased re‐operation rate and possibly increased risk of recurrence 6,7 . Finally, WGL requires separate lymphatic mapping to identify sentinel nodes which is often done using an arguably inferior subareolar radioisotope injection technique to avoid interacting with the hookwire 8 …”
Section: Introductionmentioning
confidence: 99%
“…The total number of mastectomies needed to achieve satisfactory margins in patients after initial WGL was 10 (19.6%), as compared to the 20% reported in the literature. 18 There were two additional patients who underwent re-excisional lumpectomies after initial negative margins to obtain more satisfactory negative margins.…”
Section: Discussionmentioning
confidence: 99%
“…The complete removal of neoplasia and resection margins that are pathologically free of disease are the most important factors for reducing the rate of ipsilateral breast cancer recurrence after BCS [34][35][36]. For this purpose, it is important to obtain precise information on tumor location and extent in order to resect the pathological tissue with proper surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with those reported in other studies on preoperative localization methods. Medina-Franco et al, in a study comparing ROLL versus WGL, reported that both techniques resulted in 100% retrieval of the lesions [36,37]. Ngo et al reported an identification of lesions in 95.7% of patients using IOUS [38].…”
Section: Discussionmentioning
confidence: 99%